(untitled) (Vietnam Journal of Community Medicine, 2022)
Background – aims: Sepsis is the leading cause of neonatal mortality. This study aimed to evaluate treatment outcomes and understand some factors related to mortality of full-term neonates with sepsis treated at the National Children’s Hospital (2019-2021).Method: Clinical intervention and evaluation of the effectiveness of a treatment regimen on newborns at the Neonatal Center - National Children’s Hospital who met the criteria for sepsis diagnosis with positive blood culture results.Results: There were 85 full-term neonates with sepsis. Survival rate was 69.4%, neurological sequelae 1.2%, mortality was 30.6%. Average treatment day were 23.1 ±19.8 days. The early infection group had a higher mortality rate (36.5%) than the late infection group (21.1%). The mortality rate in the group of children infected with Gram-negative bacteria was 40.9%, in the group with Gram-positive an fungal infectio were 12.1% and 50%. Factors related to outcomes: front-line mechanical ventilation, mechanical ventilation and central catheterization, septic shock, white blood cells < 4x109 cells/L, platelets < 100x109cells/L.Conclusion: Neonatal sepsis mortality was still high. Some factors associated with neonatal mortality included mechanical ventilation, central catheterization, septic shock, white blood cells < 4x109 cells/L, platelets < 100x109 cells/L